Protection of Financial Consumers Through Setting Standard Clauses in Law Number 4 of 2023 concerning Strengthening and Development of the Financial Sector - Larasati, Nieke (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
Consumers are often in a weaker position compared to business actors because consumers as a party need to understand in depth the business of a financial product or service. This study aims to determine the protection of financial consumers by setting standard clauses. This study uses a doctrinal research method. The results of this study, a form of consumer protection carried out in the law, are through regulation regarding standard agreements with standard clauses. The P2SK Law does not prohibit PUSK from using standard agreements in their business activities. Still, it regulates the prohibition of standard clauses that are felt not to fulfill the principles of balance and justice so that they have the potential to harm consumers as a party with a weaker position than PUSK. In this case, there must be a balanced relationship between PUSK and consumers, beginning with both parties' good faith. In addition, law enforcement efforts are also required through supervision by the financial sector authorities to ensure the application of consumer protection provisions by PUSK and the imposition of sanctions if there are violations. Legal certainty is also needed from the consumer side if PUSK violates consumer protection provisions that harm consumers, so consumers have the right to settle disputes by applicable regulations. Keywords: Consumer; Financial Services; Law Enforcement; Businessmen